Microlithiasis of the epididymis: A case report and review of literature - Mathew Mary; Thomas Joseph (Wolters Kluwer Medknow Publications, 2008)
Microlithiasis of the epididymis, which is not associated with epididymal inflammation, is a rare entity that has been infrequently published in the literature. We report, one such case that was incidentally detected in association with prostatic adenocarcinoma.